Primary Iliopsoas Abscess and Drug-Induced Liver Injury in the Emergency Department: A Case Report - Ovidiu Alexandru Mederle; Laurentiu Sima; Daian Ionel Popa; Carmen Gabriela Williams; Diana Mitu; Dumitru Șutoi; Cosmin Iosif Trebuian; Mircea Selaru; Dan Lolos; Ana-Maria Pah; Florina Buleu (Diseases)
Background and objective: Iliopsoas abscess (IPA) is a rare condition with varied symptomology and etiology. Less than one-third of patients with IPA present in the emergency department (ED) with the traditional triad of fever, back pain, and restricted hip motion (or limp), leading to delays in diagnosis and management. Acute liver failure is also a rare clinical presentation in the ED, being associated with high morbidity and mortality. It occurs most often in young patients without pre-existing liver disease, presenting unique challenges in clinical management. Most cases currently happen because of drug-induced liver injury (DILI), mainly from acetaminophen or idiosyncratic drug reactions. This case report aims to raise awareness among healthcare professionals regarding the two atypical presentations in ED and introduce a potential differential diagnosis when evaluating patients with fever and back pain or liver enzyme elevations with or without nonspecific symptoms associated with the development of jaundice. The intention is to provide insights into the signs and symptoms that may indicate the presence of an iliopsoas abscess and prompt additional investigations. Case report: Here, we describe a case of primary iliopsoas abscess associated with drug-induced liver injury in our ED. The patient complained of pain in the left lumbar region and fatigue that started two weeks before this presentation, claiming that, during the previous night, the pain suddenly worsened. At the first clinical examination in the ED, the patient presented pain at palpation in the right hypochondriac and left lumbar regions, accompanied by fever, vomiting, and jaundice. On abdominal ultrasonography, the diagnosis of acute cholangitis was suspected. The laboratory test shows leukocytosis with neutrophilia, thrombocytosis, elevated liver enzymes, and hyperbilirubinemia with the predominance of indirect bilirubin. After analyzing the laboratory test results, we repeated and performed a more detailed anamnesis and medical history of the patient. Because of her increasing pain and persistent fever, she recognized excessive consumption in the last five days of drug-induced hepatotoxicity. We performed abdominal and pelvic computed tomography, which confirmed the diagnosis of cholelithiasis observed with the diameter of the bile duct within normal limits but also showed an abscess collection fused to the interfibrillar level of the left iliopsoas muscle, a diagnosis we most likely would have missed. The patient was hospitalized in the General Surgery Department, and surgical abscess drainage was performed. The patient’s evolution was excellent; she was discharged after 11 days. Conclusions: The case presented here exemplifies how iliopsoas abscess, a rare cause of back pain, can quickly go unrecognized, especially in the emergency department. Our experiences will raise awareness among doctors in emergency departments about this uncommon but essential diagnosis. With advancements in diagnostic tools and techniques, we hope that more cases of iliopsoas abscess will be accurately diagnosed. Moreover, no case report from the literature has presented IPA associated with DILI. This case is unique because our patient did not exhibit classic features of either pathology. This case also emphasizes the importance of a medical history that includes thorough evaluations of potential high utilization of drug-induced hepatotoxicity.